Towards the clinical use of peripheral bile acids: Recommendations to limit their preanalytical and analytical sources of variability - Joseph, Sebastian; de Buyl, Sophie; Leclercq, Isabelle A.; Serafimov, Kristian; Feron, Olivier; Clerbaux, Laure-Alix (Practical laboratory medicine, 2025)
Despite more than three decades of research, the use of peripheral bile acids as biomarkers for human liver injury remains inconclusive due to inconsistent findings. Identifying the factors contributing to the variability in published peripheral bile acid data in humans is needed to propose experimental recommendations that could enhance the robustness and reproducibility of future studies. Besides the peripheral blood bile acid data, the metadata on subject demographics (number of subjects, average age, sex distribution, health status, fasted/fed status), the blood matrix analyzed, the matrix volume analyzed, the bile acid extraction process, and analytical technique were extracted from 65 studies involving 215 patient cohorts. Bile acid concentrations in normal cohorts were found to exhibit large inter-study variability. The analytical technique used to measure bile acid concentrations, the fasted/fed status of patients at the time of sampling, the choice of blood collection matrix, the starting volume of this matrix, and the choice of protein precipitation solvent were found to be determinants of this variability. To address these determinants, procedural recommendations are proposed: liquid chromatography-tandem mass spectrometry should be used to measure absolute bile acid concentrations in 50 μl of plasma obtained from a fasted subject, with methanol as the protein precipitation solvent. A lack of studies meeting the recommended criteria makes it difficult to conclude whether variability is reduced. These recommendations must be standardized across future studies to enhance the clinical use of peripheral bile acids as biomarkers of liver injury in humans. [Display omitted] •Inconsistent peripheral bile acid data hinders their use as liver injury biomarkers.•We analyzed 65 studies and 215 patient cohorts to uncover variability determinants.•We identified preanalytical and analytical factors causing variability.•We propose specific standardized procedural recommendations for bile acid analysis.•The recommendations aim to enhance the comparability of future bile acid studies.